Morphometric Optic Nerve Head Analysis in Glaucoma Patients: A Comparison between the Simultaneous Nonmydriatic Stereoscopic Fundus Camera (Kowa Nonmyd WX3D) and the Heidelberg Scanning Laser Ophthalmoscope (HRT III) - Siegfried Mariacher; Stephanie Hipp; Robert Wirthky; Gunnar Blumenstock; Karl-Ulrich Bartz-Schmidt; Focke Ziemssen; Ulrich Schiefer; Bogomil Voykov; Kai Januschowski (Journal of Ophthalmology)
Purpose. To investigate the agreement between morphometric optic nerve head parameters assessed with the confocal laser ophthalmoscope HRT III and the stereoscopic fundus camera Kowa nonmyd WX3D retrospectively. Methods. Morphometric optic nerve head parameters of 40 eyes of 40 patients with primary open angle glaucoma were analyzed regarding their vertical cup-to-disc-ratio (CDR). Vertical CDR, disc area, cup volume, rim volume, and maximum cup depth were assessed with both devices by one examiner. Mean bias and limits of agreement (95% CI) were obtained using scatter plots and Bland-Altman analysis. Results. Overall vertical CDR comparison between HRT III and Kowa nonmyd WX3D measurements showed a mean difference (limits of agreement) of −0.06 (−0.36 to 0.24). For the CDR < 0.5 group (n=24) mean difference in vertical CDR was −0.14 (−0.34 to 0.06) and for the CDR ≥ 0.5 group (n=16) 0.06 (−0.21 to 0.34). Conclusion. This study showed a good agreement between Kowa nonmyd WX3D and HRT III with regard to widely used optic nerve head parameters in patients with glaucomatous optic neuropathy. However, data from Kowa nonmyd WX3D exhibited the tendency to measure larger CDR values than HRT III in the group with CDR < 0.5 group and lower CDR values in the group with CDR ≥ 0.5.